Effect of Basal Testosterone and Dehydroepiandrosterone Sulphate Levels on in Vitro Fertilization Outcome in Normoresponders - Kahyaoğlu, İnci; Yılmaz, Nafiye; Kahyaoğlu, Serkan; Türkkanı, Ayten; Çiçek, Mahmut Nedim; Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVE: The purpose of the present study is to evaluate the predictive value of basal total testosterone (total-T) and dehydroepiandrosterone sulphate (DHEAS) levels in normoresponder patients undergoing IVF-ET. STUDY DESIGN: A total of 60 normoresponder infertile women, scheduled to undergo their first IVF/ET cycle were enrolled in this study. Day 2-4 basal concentrations of FSH, LH, E2, total testosterone, DHEAS and antral follicle count (AFC) were determined in preceding cycle. RESULTS: No significant difference was found between pregnant and non-pregnant groups regarding the AFC, hormone and controlled ovarian hyperstimulation (COH) parameters (total dose of gonadotrophins (1995.7±851.1 vs 2296.4±845.3 IU), >14 mm follicles (9.3±3.1 vs 7.3±3.9), retrieved oocytes (12.4±5.1 vs 8.7±6.1) or number of good quality embryos (7.4±3.7 vs 4,4±3.6) (p>0.05). Testosterone and DHEAS was not correlated with COH parameters (p>0.05). CONCLUSION: There is no correlation between testosterone and DHEAS levels and COH parameters in normoresponder IVF patients.